STUDY OF ARTIFICIAL FISH APARTMENT (AFA)âS VERTICAL GAP CONFIGURATION AS A SOLUTION FOR COASTAL EROSION IN TIRANG BEACH SEMARANG - Mustaqim, Rahim
Tirang Beach have been suffering from deterioration of the coastline due to hydrodynamic condition such as tide, current, wave, and sediment transport. The implementation of Artificial Fish Apartment or AFA from Dinas Perikanan Kota Semarang was analyzed through sediment deposition from 14 observation points at the site. Observation point were zoning based on the similarity of sediment deposition characteristic at different modelling scenario. The AFA’s structure has a shape like a porous submerged breakwater, arrangement of 50 cm x 50 cm x 50 cm porous cube along 400 m. The distance between the beach and structure about 850 m for AFA-A and 670 m for AFA-B. The porosity of AFA’s structure reach 60%. The AFA’s structure was modeled using the obstacle function and coupling between Delft3D-Flow and Delft3D-Wave. The driving forces at the open boundary were TPXO 7.2 tide konstituent, SPM 1984 hindcasting wave from NOAA wind data, cohesive sediment concentration of 0.05 kg/m3, salinity concentration of 32.85 ppt, and Silandak River discharge and sediments of 0.87 m3/s and 0.37 kg/m3. The modeling was carried out for 1 month with several scenarios which are existing or 0, 1, 2, and 3 based on AFA’s top elevations of 0 m, 1.5 m, 3.0 m, and 4.5 m as well as gap with MSL water level elevations of 5 m, 3.5 m (Rc/Hi = 7.89), 2 m (Rc/Hi=4.51), and 0.5 m (Rc/Hi=1.13). The result from the modelling show that only scenario 3 with AFA’s height about 4.5 m and 0.5 m gap from MSL elevation (Rc/Hi = 1.13) can deposite sedimen on zona 1, zona 2, and zona 3 at study location. The rate of deposition reach 0.50 – 0.93 cm/ month.